2014
DOI: 10.1002/ejoc.201402170
|View full text |Cite
|
Sign up to set email alerts
|

A Three‐Step Synthesis of the Guaianolide Ring System

Abstract: By using a gallium(III) triflate catalyzed intramolecular (4+3) cycloaddition, a few functionalized furan‐derived tricycles that share the common guaianolide sesquiterpene ring system were prepared in a stereoselective manner in only three steps from commercially available starting materials. A discussion of the formation of alternative products is included, with possible substrate requirements to achieve the key cycloaddition step in an efficient way.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…Previously, it was shown that feverfew P450s acting on germacrene A, germacrene A acid, costunolide and parthenolide all belong to the CYP71 family 11 14 , 18 . Moreover, the genes encoding the enzymes of the parthenolide biosynthesis pathway ( TpGAS 13 , TpGAO 13 , TpCOS 13 and TpPTS 19 ) show a distinct expression profile during feverfew ovary development, matching with the accumulation profile of parthenolide 11 , 13 , 14 (Supplementary Fig. 1a ).…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Previously, it was shown that feverfew P450s acting on germacrene A, germacrene A acid, costunolide and parthenolide all belong to the CYP71 family 11 14 , 18 . Moreover, the genes encoding the enzymes of the parthenolide biosynthesis pathway ( TpGAS 13 , TpGAO 13 , TpCOS 13 and TpPTS 19 ) show a distinct expression profile during feverfew ovary development, matching with the accumulation profile of parthenolide 11 , 13 , 14 (Supplementary Fig. 1a ).…”
Section: Resultsmentioning
confidence: 94%
“…1a ). The costunolide 3β-hydroxylase 19 , though, displays a slightly different expression profile (Supplementary Fig. 1a and 1b ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A very recent strategy was presented by Winne et al, [71] who assembled the guaianolide ring system in three straightforward synthetic operations by using a highly diastereoselective intramolecular [4+3] cycloaddition reaction of a catalytically generated furfuryl cation intermediate. The first precursor was generated in two steps by treating the anion derived from furan β-keto ester 176 with bromodiene 175.…”
Section: Hydroazulene-lactone Strategies Involving Intramolecular Cycmentioning
confidence: 99%
“…This key step has been reported for the synthesis of promising products such as seco-guaianolides and dimeric guaianolides. [71] Other useful synthetic methodologies such as MARDi cascade, transition-metal catalysis, or ring-closing metathesis have also been introduced.…”
Section: Hydroazulene Strategies Based On Intermolecular Cycloadditionmentioning
confidence: 99%